Improved 93-11 Genome and Time-Course Transcriptome Expand Resources for Rice Genomics - Wang, Sen; Gao, Shenghan; Nie, Jingyi; Tan, Xinyu; Xie, Junhua; Bi, Xiaochun; Sun, Yan; Luo, Sainan; Zhu, Qianhui; Geng, Jianing; Liu, Wanfei; Lin, Qiang; et al. (Frontiers in Plant Science, 2022)
In 2002, the first crop genome was published using the rice cultivar 93-11, which is the progenitor of the first super-hybrid rice. The genome sequence has served as a reference genome for the indica cultivars, but the assembly has not been updated. In this study, we update the 93-11 genome assembly to a gap-less sequence using ultra-depth single molecule real-time (SMRT) reads, Hi-C sequencing, reference-guided, and gap-closing approach. The differences in the genome collinearity and gene content between the 93-11 and the Nipponbare reference genomes confirmed to map the indica cultivar sequencing data to the 93-11 genome, instead of the reference. Furthermore, time-course transcriptome data showed that the expression pattern was consistently correlated with the stages of seed development. Alternative splicing of starch synthesis-related genes and genomic variations of waxy make it a novel resource for targeted breeding. Collectively, the updated high quality 93-11 genome assembly can improve the understanding of the genome structures and functions of Oryza groups in molecular breeding programs.